Kesepian dan Kecerdasan Emosi pada Mahasiswa yang Kembali ke Kost Pasca Pandemi Covid-19 - Christine Kurniawati; Eli Prasetyo (Psychopreneur Journal, 2024)
After the current Covid-19 pandemic, the field of education is entering a new period of adaptability in which students are resuming offline learning. As a result, out-of-town overseas students are forced to return to their boarding houses and are cut off from their relatives. Overseas students endure emotions of isolation regularly. Loneliness is a feeling that individuals experience when they desire social ties in their environment but cannot achieve them. This relates to the various sorts of loneliness, such as when an individual does not receive the desired social life, loneliness resulting from personality patterns, and loneliness resulting from the individual's unpleasant feeling condition (Russell, 1996). Individuals who lack emotional intelligence as a defense and protection against unpleasant emotions, such as loneliness, will see a deterioration in their feelings of isolation. The existence of emotional intelligence is extremely beneficial for interpersonal connections. In addition, emotional intelligence encompasses detecting others' emotions, managing them, developing relationships, and motivating oneself (Salovey & Mayer, 1990). Consequently, this research aims to evaluate the association between loneliness and emotional intelligence in students returning to boarding schools after the Covid-19 pandemic. The research will involve 116 participants aged 18 - 25. The UCLA Loneliness Scale, Version 3, and the Schutte Emotional Intelligence Scale (SEIS) were used in this research to collect data. Pearson Product Moment Correlation is the parametric statistical technique used to examine the relationship between the two research variables. Based on the results of hypothesis testing on the variables of loneliness and emotional intelligence, it can be demonstrated that the value of r = -0.339 with p-value = 0.000<0.05. The results of this research show that there is a negative correlation between loneliness and emotional intelligence among students who return to boarding houses following the pandemic. The more emotional intelligence an individual possesses, the less loneliness they experience, and vice versa.